Preparation of high-performance flexible microsupercapacitors based on papermaking and laser-induced graphene techniques. (1st January 2022) - Wang, Min; Chen, Junjun; Lu, Kuanbin; Ma, Ying; Li, Hailong; Ye, Jianshan
Highlights: MSCs were prepared via the papermaking and laser-induced graphene techniques. The MSCs exhibit good areal specific capacitance and mechanical flexibility. This strategy enables the massive production of MSCs. The as-prepared MSCs can be widely applied in energy storage devices. Abstract: We report a new method to prepare high-performance flexible microsupercapacitors (MSCs) via the combination of papermaking technique and laser-induced graphene (LIG) technique. The papermaking technique allows the massive production of poly( p -phenylene benzobisoxazole) (PBO) paper, and the LIG process can directly convert the PBO paper into graphitized material. The resulting material exhibits excellent capability as electrode materials for MSCs thanks to the highly graphitized degree of PBO paper to improve the conductivity of the electrode and the formation of excessive nano-sized bumps to increase the surface area, which are two crucial factors for good MSCs. The largest areal specific capacitance can reach as high as 46.3 mF cm −2 and is 12 times higher compared to that of MSCs prepared with the polyimide (PI) as a LIG substrate. The MSCs prepared from different PBO papers demonstrate high reproducibility, and the maintenance of 85% specific capacitance after 3000 cycles bending tests reveals their excellent flexibility. Owing to the high-performance capacitance, easy preparation, and massive production of MSCs, we envision that this technique can be widely applied for the preparation of energy storage devices. Graphical abstract: Image, graphical abstract